2013
DOI: 10.1080/02755947.2013.763878
|View full text |Cite
|
Sign up to set email alerts
|

Channel Unit Use by Smallmouth Bass: Do Land‐Use Constraints or Quantity of Habitat Matter?

Abstract: I examined how land use influenced the distribution of Smallmouth Bass Micropterus dolomieu in channel units (discrete morphological features—e.g., pools) of streams in the Midwestern USA. Stream segments (n = 36), from four clusters of different soil and runoff conditions, were identified that had the highest percent of forest (n = 12), pasture (n = 12), and urban land use (n = 12) within each cluster. Channel units within each stream were delineated and independently sampled once using multiple gears in summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…In a study of Ohio streams, Miltner and Rankin (1998) observed the highest fish abundances at intermediate nutrient concentrations, whereas abundances of sensitive species were reduced at higher concentrations. Smallmouth Bass and Brook Trout have both been shown to be sensitive to habitat degradation (Sowa and Rabeni 1995;Argent and Flebbe 1999;Curry and MacNeill 2004;Stranko et al 2008;Brewer and Rabeni 2011;Brewer 2013), pointing to one mechanism by which nutrient enrichment could be a stressor on fish. High concentrations of growth-limiting plant nutrients have been linked to an excessive growth of algae, macrophytes, and phytoplankton, which in turn can change habitat structure, flow velocities, dissolved oxygen concentration, and pH (Welch et al 1992;Dodds and Biggs 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In a study of Ohio streams, Miltner and Rankin (1998) observed the highest fish abundances at intermediate nutrient concentrations, whereas abundances of sensitive species were reduced at higher concentrations. Smallmouth Bass and Brook Trout have both been shown to be sensitive to habitat degradation (Sowa and Rabeni 1995;Argent and Flebbe 1999;Curry and MacNeill 2004;Stranko et al 2008;Brewer and Rabeni 2011;Brewer 2013), pointing to one mechanism by which nutrient enrichment could be a stressor on fish. High concentrations of growth-limiting plant nutrients have been linked to an excessive growth of algae, macrophytes, and phytoplankton, which in turn can change habitat structure, flow velocities, dissolved oxygen concentration, and pH (Welch et al 1992;Dodds and Biggs 2002).…”
Section: Discussionmentioning
confidence: 99%
“…We electrofished areas that were at least 0.2 m deep in an upstream direction with a zigzag pattern. The depth limitation of the tow-barge electrofisher excluded most riffle areas, but the use of that habitat by Smallmouth Bass larger than 80 mm TL is very uncommon (Brewer 2013; Oklahoma Department of Wildlife Conservation [ODWC], unpublished snorkel data). Care was taken to thoroughly electrofish areas with structure (e.g., large wood, root wads, and boulders).…”
Section: Methodsmentioning
confidence: 99%
“…So what are resource managers to do? It may be best to focus on riparian rehabilitation because that habitat has the most well-documented effects on stream condition (Naiman and Decamps 1997), and it also confers local habitat benefits at the reach scale (Brewer 2013). However, we note three caveats: (1) riparian rehabilitation can take many forms, depending on local physiographic conditions (a.k.a.…”
Section: Bank Stabilizationmentioning
confidence: 99%
“…(2) in many watersheds extensive impervious surface coverage can override riparian services (Coles et al 2012); and (3) extensive pipe networks can bypass riparian zones (Brewer 2013).…”
Section: Bank Stabilizationmentioning
confidence: 99%
See 1 more Smart Citation